2017
DOI: 10.1152/ajpgi.00444.2016
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide improves intestinal recovery following ischemia by endothelial nitric oxide-dependent mechanisms

Abstract: Hydrogen sulfide (HS) is an endogenous gasotransmitter that has vasodilatory properties. It may be a novel therapy for intestinal ischemia-reperfusion (I/R) injury. We hypothesized that ) HS would improve postischemic survival, mesenteric perfusion, mucosal injury, and inflammation compared with vehicle and ) the benefits of HS would be mediated through endothelial nitric oxide. C57BL/6J wild-type and endothelial nitric oxide synthase knockout (eNOS KO) mice were anesthetized, and a midline laparotomy was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…While it is clear that ischemic insult alone does not result in NEC, further investigation into the salvage effects of H 2 S can be bolstered by evaluation of treatment of intestinal ischemia reperfusion (I/R) injury, a much more exact and reproducible model. Previous work has shown that sodium hydrosulfide (NaHS), a H 2 S salt, is protective against intestinal I/R injury in adult mice [10], and similar benefits have been demonstrated in experimental NEC with other hydrogen sulfide donors [11].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…While it is clear that ischemic insult alone does not result in NEC, further investigation into the salvage effects of H 2 S can be bolstered by evaluation of treatment of intestinal ischemia reperfusion (I/R) injury, a much more exact and reproducible model. Previous work has shown that sodium hydrosulfide (NaHS), a H 2 S salt, is protective against intestinal I/R injury in adult mice [10], and similar benefits have been demonstrated in experimental NEC with other hydrogen sulfide donors [11].…”
Section: Introductionmentioning
confidence: 78%
“…In an intestinal I/R model, the benefit conferred by the NaHS was shown to be dependent on endothelial nitric oxide [10]. Endothelial cells constitutively express the enzyme endothelial nitric oxide synthase (eNOS), which produces the gasotransmitter nitric oxide (NO) [12].…”
Section: Introductionmentioning
confidence: 99%
“…NaHS, a donor for H 2 S, significantly attenuates pulmonary iNOS activation in ovalbumin-treated rats (Chen et al, 2009). Moreover, H 2 S is found to act as an anti-inflammatory agent contributing to gastrointestinal mucosal defense through NO-dependent pathway (Jensen et al, 2017). In cardiovascular system, vasodilation is impaired and endothelial H 2 S content is decreased in vessels from obese mice, this may be attributed to the increased iNOS activity in proinflammatory macrophages (Candela et al, 2017).…”
Section: Evidence For H 2 S/no Crosstalk In Endothelial Inflammationmentioning
confidence: 99%
“…Inflammation plays a significant role in inducing liver injury and driving the progression of NAFLD [12]. Numerous reported evi-dences have highlighted the anti-inflammation properties of endogenous H 2 S in the liver, kidney, small intestine, pancreas, lung, brain tissues and immune cells [11,[13][14][15][16][17][18]. Here, we investigated for the first time the anti-inflammation properties of H 2 S in an independent setting in PA-induced HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%